(untitled) (Annals of Medical Research, 2022)
Aim: Hand hygiene has become an important building block in the prevention of the spread of coronavirus disease 2019 (COVID-19). The current study was conducted to determine the hand hygiene habits of healthcare workers and possible risk factors for hand eczema during the COVID-19 pandemic. Materials and Methods: The hand hygiene habits of healthcare personnel working at a university hospital since COVID-19 pandemic started were questioned between December 2020 and February 2021 and they were dermatologically examined to screen for hand eczema. Results: Of the 150 healthcare workers, 56 (37.3%) were doctors and 94 (62.7%) were nurses, and 40 (26.7%) were men and 110 (73.3%) were women. The rate of participants that reported washing their hands more frequently than 25 times daily was 46.0% (n=69), and the rate of disinfectant use was 59.3% (n=89). While 88 (58.7%) of the participants used a moisturizer daily, 62 (41.3%) did not use a moisturizer. Fifteen (10.0%) participants were diagnosed with hand eczema. Conclusion: There was an increase in the daily frequencies of hand washing and use of disinfectants during the COVID-19 pandemic, but our data did not reveal any statistically significant risk factor of hand eczema.